Stroke in the Very Old: A Systematic Review of Studies on Incidence, Outcome, and Resource Use - Tommasina Russo; Giorgio Felzani; Carmine Marini (Journal of Aging Research)
Background and Purpose. Stroke incidence increases with age and is likely to increase in the aging populations. We investigated incidence, outcome, and resource use in very old subjects with stroke. Methods. We performed a systematic review of available data through electronic search of the literature databases and manual search of reference lists. Data were extracted for the age groups of over 80, 80 to 84 years old, and over 85. Overall incidence rates, expressed as the number of first strokes per 1000 person-years, were estimated using Poisson regression analysis. Odds ratios for the comparisons between subjects over and under 80 were calculated with the Mantel-Haenszel method. Results. We found a high incidence of stroke in the very old. The estimated incidence rates were 20.78 (95% CI 19.69 to 21.87) in subjects over 80, 17.23 (95% CI 15.97 to 18.49) for those 80 to 85 years old, and 20.78 (95% CI 16.74 to 23.78) for those over 85. Subjects over 80 contributed 29.95% of strokes; rates were similar among genders. Thirty-day case fatality rate and occurrence of dependency were higher in subjects over 80, although associated with less frequent hospital and stroke unit admission and less diagnostic resource use. Conclusions. The contribution of very old subjects to the global burden of stroke is relevant and may require efficient dedicated stroke services.